Senior School Students' Low Perfomance: Teachers' Beliefs - X.A. Tursunbayeva; Sh.O. Tazabek; A.A. Chsherbakov (Moscow State University of Psychology and Education, 2023)
The article presents the results of a study that explores the teachers’ beliefs concerning low-performing senior schoolchildren in one of the regions of Kazakhstan. Until recently, the issue of low-achieving students was largely absent from the agenda of secondary education and has not got attention from Kazakhstani researchers. A case study methodology was applied as the principal research method, facilitating an in-depth examination of teachers’ belief systems concerning low-performing students. 22 high school and first-year college teachers participated in a qualitative study in May and June 2022. We analyzed teachers’ ideas about low-achieving students within an ecological framework using an inductive thematic analysis of individual interviews and focus group discussions. We identidied the categories of teachers’ individual, in-school and systemic beliefs. These beliefs collectively contribute to the conceptualisation of a low-performing students, their educational trajectories, and their potential for success or failure in life.